2015
DOI: 10.1016/j.molstruc.2014.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure studies of (1S,2S)-2-benzyl-2,3-dihydro-2-(1H-inden-2-yl)-1H-inden-1-ol

Abstract: HighlightsChemical separation is used for racemate resolution.NMR analyses are used for single enantiomer structure education.Intermolecular interactions are observed by X-ray study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 23 publications
(29 reference statements)
0
37
0
Order By: Relevance
“…Compounds PH21and PH22 are single enantiomers separated from PH5, being ( 1R, 2R ) and ( 1S, 2S ) ‐2‐benzyl‐2,3‐dihydro‐2‐(1H‐inden‐2‐yl)‐1H‐idnen‐1‐ol), respectively. Details of the synthesis, separation, characterisation and confirmation of structure by X‐ray diffraction of these compounds are described elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds PH21and PH22 are single enantiomers separated from PH5, being ( 1R, 2R ) and ( 1S, 2S ) ‐2‐benzyl‐2,3‐dihydro‐2‐(1H‐inden‐2‐yl)‐1H‐idnen‐1‐ol), respectively. Details of the synthesis, separation, characterisation and confirmation of structure by X‐ray diffraction of these compounds are described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Details of the synthesis, separation, characterisation and confirmation of structure by X-ray diffraction of these compounds are described elsewhere. [11,12,19] A total of 123 mice were used in this study. All animal research work reported in this article have been carried out in the Comparative Medicine Unit, Trinity College Dublin, a Health Products Regulatory Authority (HPRA) approved establishment that operates in accordance with Directive 2010/63/EU and its Irish transposition S.I No 543 of 2012.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PSA, PXRD, DSC, and TGA analysis of PLGA were performed. The PXRD analysis of PLGA powder sample was performed with the help of Rigaku MiniFlex-II Desktop X-ray diffractometer (Japan) [34,35] . The average size of crystallites was calculated from PXRD data using the Scherrer's formula (1)…”
Section: Characterizationmentioning
confidence: 99%
“…The PSA was carried out using Malvern Mastersizer 2000 (the UK) with the help of the wet method [35,36]. The PXRD analysis of WS root extract was performed with the help of Rigaku MiniFlex-II Desktop X-ray diffractometer (Japan) [37,38]. The average size of the crystallite was calculated from PXRD data using the Scherrer's formula (1) Trivedi…”
Section: Characterizationmentioning
confidence: 99%